History of Chinese Communities in the District Aru Islands - Kissiya, Efilina (Guidance and Counseling Study Program, Pattimura University, 2019)
Ethnicity Chinese is group society nomads who almost occupy all over Indonesian territory arrived in remote areas even though even ethnicity this is almost too occupy all countries in the world. Existence of ethnicity Chinese in Aru has a long history and very interesting for examined. The Problem in research this is: how history society Chinese in the District The Aru Islands with use Method historical research. Historian England, Robin George Collingwood (1889-1943), gave three understanding about history, namely: (1) all history is history thinking, (2) knowledge history is enforcement back thought in mind historians whose history is being studied , and (3) knowledge history is a business inviting back thoughts of the past are wrapped up in context thoughts today are with contradict it, limit it from different fields from field them (Collingwood 2004: 134-139). It seems Collinwood is more emphasis on history thoughts and how the historian uses his mind to understand various things that are in event history. Way of thinking this is also dominant in thought the history of Michel Foucault (1926-1984) who tended to the history of ideas or thought (Foucault 2002). He admitted that history Indeed is ' cheap ' fields to anyone who wants to learn it, but on him also there space astray for those who aren't able to dive in room knowledge history in a manner deep particularly related with network knowledge unvisible. Research results showing that: Arrival ethnicity Chinese in Aru are caused because of reason economy because the difficulty life economy in China are urging the community to do migrant Exit from China. Aru with various results earth especially results in the sea that is pearls, Lola, sea cucumbers, and fish and bird paradise make Pull the power itself alone for migrants including ethnicity Chinese. Social adaptation conducted by ethnicity Chinese to the Aru community is very binding life social The Aru community own because ethnicity Chinese in life daily not create differently or distance between they are.